Succession of Fungal Community Structure in Degradative Land Caused by Basal Rot Pathogen of Garlic - Cahyani, Vita Ratri; Rahayu, Devi Puji; Siswanto, Agus; Prasetyo, Dedy; Hadiwiyono, Hadiwiyono (Faculty of Agriculture, Sebelas Maret University, 2014)
Land degradation causes a decreasement the ability of land in suppressing the development of pathogen FOCe that causes basal rot of garlic. In the garlic planting area in Tawangmangu discovered the fact that productive-suppressive land to FOCe the disease has low incidence (<1%) and degradative-conducive land with high incidens (â¥60%). The research aims to study the succession of common fungal community structure and FOCe in the rhizosphere of garlic on both land for garlic plantation. The study was conducted from April to September 2013 in productive-suppressive land (Pancot) and degradative-conducive (Gondosuli) for soil sampling and laboratory analysis in Biologi Tanah UNS for fungi and FOCe analysis. The composite method used for sampling and the garlic rhizosphere samplesÂ which is had healthy plants conditions aged 0, 20, 40, and 60 days after planting (DAP), and the garlic rhizosphere samples with healthy plants and diseased condition aged 80, 100, and 120 days after planting (DAP). Laboratory analysis using PDA culture medium as common fungi growing medium and SFA as a growing medium FOCe then observed population density and diversity. The method was pour plate method with 10-2 to 10-7 dilution. The results showed the population and diversity of fungi and FOCe have dynamics fluctuation. The fungi population in productive-suppressive land lower than degradative-conducive, with each value 108 and 3,5x108 CFU gram-1 soil. FOCe population on degradative-conducive land was higher than productive-suppressive land, and the highest population in both land at age 20 and 100 DAP with a FOCe density of each land about 1,25x107 and 1,66x107 CFU gram-1 soil. During the growth periode of garlic, the fungi diversity on productive-suppressive land always indicate higher than degradative-conducive land.